Effects of platelet-rich plasma gel on vaginal microecology and stump healing and its underlying mechanism - Wang, Mingyang; Peng, Yunbi; Zhou, Li; Liu, Hong; Zou, Xiaofeng; Wang, Zhiliang (Frontiers in Medicine, 2026)
ObjectiveThe study aimed to explore the effects of platelet-rich plasma (PRP) gel on vaginal microecology and stump healing, as well as its underlying mechanism.MethodsFrom December 2022 to August 2024, 100 patients who underwent laparoscopic hysterectomy at our hospital were selected and divided into an observation group and a control group. The control group received the conventional suture method, while the observation group received PRP glue applied between the reflexive peritoneum and the vaginal stump in addition to the conventional suture.ResultsCompared to the control group, the observation group had a higher rate of grade A healing (p < 0.05) and a lower rate of bleeding and granulation in the vaginal stump (p < 0.05). One month after surgery, compared to the control group, the observation group had a greater number of patients with cleanliness levels I-II, a smaller number of patients with cleanliness level IV, a smaller number of patients with pH values > 4.5, and lower positive rates of sialic acid enzyme activity, hydrogen peroxide concentration, and leukocyte esterase activity (p < 0.05). The total pathogen infection rate in the observation group was lower than that in the control group (p < 0.05). Furthermore, 3 days after surgery, compared to the control group, the observation group had lower levels of CRP, IL-6, IL-11, IL-21, and IL-2, as well as lower levels of toll-like receptor 4 (TLR4) and MBL (p < 0.05).ConclusionPRP gel can improve vaginal microecology and promote the healing of the vaginal stump in patients undergoing laparoscopic hysterectomy. However, further research is needed to fully understand the underlying mechanisms and confirm its long-term effects.